Increasing Compound Heat and Precipitation Extremes Elevated by Urbanization in South China - Wu, Sijia; Chan, Ting On; Zhang, Wei; Ning, Guicai; Wang, Peng; Tong, Xuelin; Xu, Feng; Tian, Hao; Han, Yu; Zhao, Yongquan; Luo, Ming (Frontiers in Earth Science, 2021)
Compared with individual events, compound weather and climate extremes may impose more serious influences on natural systems and human society, especially in populated areas. In this study, we examine the changes in the compound precipitation events that follow extremely hot weather within several days during 1961–2017 in South China by taking the Guangdong Province as an example. Additionally, we assess the impacts of urbanization on these changes. It is found that extreme precipitation events in Guangdong are often preceded by hot weather, with an average fraction of 28.25%. The fraction of such compound events is even larger in more populated and urbanized areas such as the Pearl River Delta (PRD) region. Moreover, our results reveal significant increases in the frequency and fraction of the compound extreme heat and precipitation events. These increases are especially stronger in more developed areas (e.g., PRD), and their increasing trends tend to accelerate in recent decades. Furthermore, the local urbanization contributes to 40.91 and 49.38% of the increases in the frequency and fraction of the compound events, respectively. Our findings provide scientific references for policy-makers and urban planners to mitigate the influences of the compound heat and precipitation extremes by considering their increasing risks under the context of global climate change and local urbanization.